Clinical Effectiveness of Ion-Releasing Restorations versus Composite Restorations in Dental Restorations: Systematic Review and Meta-Analysis - Heber Isac Arbildo-Vega; Fredy Hugo Cruzado-Oliva; Franz Tito Coronel-Zubiate; Sara Antonieta Luján-Valencia; Joan Manuel Meza-Málaga; Rubén Aguirre-Ipenza; Adriana Echevarria-Goche; Eduardo Luján-Urviola; Tania Belú Castillo-Cornock; Katherine Serquen-Olano; Carlos Alberto Farje-Gallardo (MDPI AG, 2024)
Background: To compare the clinical effectiveness of ion-releasing restorations (IRR) vs. composite resin (CR) in dental restorations. Methods: A systematic search was carried out from articles published until January 2024, in the biomedical databases: PubMed, Cochrane Library, Scielo, Scopus, Web of Science and Google Scholar. Randomized clinical trials were included, with a follow-up time greater than or equal to 1 year, without time and language limits and which reported the clinical effect of IRR compared to CR in dental restorations. The RoB 2.0 tool was used to assess the risk of bias of the included studies and the GRADEPro GDT tool was used to assess the quality of evidence and the strength of recommendation of the results. Results: The search yielded a total of 1109 articles. After excluding those that did not meet the selection criteria, 29 articles remained for the quantitative synthesis. The analysis found no statistically significant difference when comparing the dental restorations with IRRs or CRs. Conclusion: The literature reviewed suggests that there are no differences between the IRRs and CRs in dental restorations.